Uncertainty evaluation and phase variation of ultrasonic interferometer manometer: A primary pressure and vacuum standard. (July 2019) - Kumar, Ashok; Thakur, Vikas N.; Sharma, Rakesh; Kumar, Harish; Omprakash,; Yadav, Sanjay
Abstract: The ultrasonic interferometer manometer (UIM) is an apex level primary pressure standard for Pascal realization established at National Physical Laboratory India (NPLI). The performance of UIM has been evaluated from time to time by participation in key comparisons, calibration and measurement capabilities (CMC) and publications in reputed international metrology journals. The pressure is measured using time of flight technique at 44 different frequencies in ultrasonic range and the phase measurement. The phase measurement combined with the time of flight measurement using the exact fractional algorithm provides highly accurate column length hence respective pressure values. The combined process helps in lowering the uncertainty in real experimental conditions. Recently, we have also changed UIM software from tbasic to window based program with the same algorithm which provides a column length measurement study. A detailed study was carried out for variation of fringe counts or oscillations with varying pressure. Experimental and theoretical calculation for both resolution and pressure dependent part has been carried out for uncertainties involves the physical parameters. The uncertainties in lower pressure range, i.e., between 1 Pa and 1000 Pa were varying equal or sometimes higher than the theoretical resolution value 0.0092 Pa ( k = 2) because of environmental conditions like vibration, temperature, atmospheric pressure, and humidity whereas for higher pressure range, i.e., 1000 Pa to 130 kPa the uncertainties were either close or smaller than the pressure dependent theoretical uncertainty value, i.e. 7.2 × 10 −6 of the reading. Highlights: We report state of art primary pressure standards with ppm level of uncertainties in measurement. The experimental and theoretical expanded relative uncertainties at k = 2 are 5.6 ppm and 7.2 ppm, respectively. The amplitude and wavelength of the received echo varies inversely with pressure/column of length. Experimental as well as theoretical uncertainties are in close agreement in the range of 1 Pa–130 kPa. The UIM shows long term stability in pressure measurement with 7.2 ppm of uncertainty since last 36 years.